A FORMAÇÃO DE ATITUDES LEITORAS NAS CRIANÇAS DE EDUCAÇÃO INFANTIL: Mediação pedagógica e participação da criança - MONTELES, Itacira Mouzinho Lima (2024)
The main objective of this study is to understand how the process of appropriation of reading attitudes occurs by children aged five and six in a public early childhood education institution. As for the specific objectives there are: 1) To understand the reading experiences made possible to children through pedagogical mediation; 2) Verify the meanings attributed by children to reading, through cultural experiences with this language in Kindergarten II; 3) Characterize the reading attitudes appropriated by children in Kindergarten II. These objectives began with concerns felt by this researcher in her pedagogical work that resulted in the following question: how do five and six year old children appropriate reading attitudes mediated in early childhood education contexts? As fundamental contributions to understanding some aspects of the formation of reading attitudes in children aged five and six in early childhood education, this research seeks support in the theoretical framework of Historical- Cultural Theory in dialogue with Bakhtin and other reading scholars. The study carried out seeks to locate the children's experience in contexts - historical and cultural - lived in the institution and, for this, ethnographic research offers possibilities of approaching the child, their interactions and practices due to their sensitivity to the singularities and differences that constitute being a child, therefore, the researcher participates in the research with the child, in a movement of rapprochement and construction of knowledge. This research lasted four months, between September and December 2023. Participatory observation was used through interpretative research using data generation instruments: field notebook, image records, videos and audios. The treatment of data gerated in the field study, with twenty-two (22) children from the Kindergarten II class in the morning shift from the Olinda Desterro Basic Education Unit of the Municipal Education Network of São Luís - MA, was done through the use of the WebQDA software and the analysis was through narrative description and qualitative interpretation of the data, relating them to the contexts verified in the research field and the comprehension of the theoretical frames of reference. As results, it can be pointed out that the child's reading formation is driven by the children's needs and interests and that these factors are linked to the production of meaning in a process of interaction and participation. Furthermore, the teacher's mediation in a dialogical perspective allows children to take ownership of reading and perceive it in its social function.